2016
DOI: 10.1016/j.jclinepi.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of protocols and publications suggested that most discontinuations of clinical trials were not based on preplanned interim analyses or stopping rules

Abstract: Two-thirds of RCT protocols did not consider interim analyses, stopping rules, or DSMBs. Most RCTs discontinued for early benefit or futility were stopped without a prespecified mechanism. When assessing trial manuscripts, journals should require access to the protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…While interim analyses are published quite frequently, under-reporting of this design feature exists, and therefore the actual use rate of stopping rules is greater than it appears in the published literature [2]; a particular problem is non-reporting of even the existence of a stopping rule for studies that actually complete their target total sample sizes, without the stopping rule being invoked. We acknowledge that there were only four trials with published protocols in our sample and that we did not contact trial investigators about unreported details of potentially existing stopping rules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While interim analyses are published quite frequently, under-reporting of this design feature exists, and therefore the actual use rate of stopping rules is greater than it appears in the published literature [2]; a particular problem is non-reporting of even the existence of a stopping rule for studies that actually complete their target total sample sizes, without the stopping rule being invoked. We acknowledge that there were only four trials with published protocols in our sample and that we did not contact trial investigators about unreported details of potentially existing stopping rules.…”
Section: Discussionmentioning
confidence: 99%
“…We included publications of randomised controlled trials (RCTs) that (1) investigated superiority of an intervention; (2) reported early stopping of the trial in the title or abstract; and (3) explicitly reported stopping for futility in the full text. Hence, we did not consider one-arm trials, non-inferiority RCTs, or the stopping of individual trial arms while the remaining trial continued, but multi-arm trials were admissible.…”
Section: Eligibility Criteria and Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…22 Given that 60% of randomised clinical trials are eventually published, 23 we estimate that 125 trials are started daily, which is 2.5 times more than the number of trial protocols registered daily (51) in 2014-2015 on clinicaltrials.gov. About 5% of registered trials are never started, 24 and many others are terminated early (12% of those posted on clinicaltrials.gov 25 ; 28% of those approved by research ethics committees). 23 Given that many trials also have secondary Might become a source of prestige to the organisations hosting these groups…”
Section: How Big Is the Task?mentioning
confidence: 99%
“…Judging this is difficult, however. Stegart et al (46) show that most trials that are stopped on the basis of either early benefit or futility have not followed stopping rules. Part of the problem here relates to the philosophy of statistics: a frequentist approach might tend to the later termination of a trial than a Bayesian one.…”
Section: Trial Conductmentioning
confidence: 99%